Utilizing Siakad Web-Based Learning (SWBL) to Promote Creativity Performance for University Students - Siahaan, Mungkap Mangapul; Sirait, Jumaria; Purba, Yoel Octobe; Purba, Rudiarman; Simanjuntak, Harry Cristofel (Association of Language Teachers in Southeast Asia (ALTSA), 2024)
This study aimed to investigate and explore potential factors influencing the creative performance of using SIAKAD web-based learning (SWBL). This study utilised the effect of SWBL to improve students’ creative learning in English Syntactic Structure class. However, SWBL was theoretically researched, and this study's perspective enriched teachers' learning creativity. Therefore, the SWBL has been designed as a learning environment system with planning, learning, evaluation, and reflection based on attributes, processes, and learning contexts. Fifty students participated as participants that were randomly assigned to be the experimental and the control group. This study used quantitative research with a quasi-experimental design. This research method was used to determine which group was effective in helping students improve their academic achievement in English Syntactic Structure. Treatment was provided in the experimental group by conducting English Syntactic Structure on the SWBL while the control group was performing a lecturing learning class. The data were analyzed by using tcount and ttable. The final data was evaluated using the Statistical Product and Service Solution (SPSS 23). The result of this study indicated that the students using the SWBL in the English Syntactic Structure class exhibited significant improvement in creativity performance. The experimental class students who used web-based learning scored 16.111 higher than the control class. Furthermore, the SWBL capabilities of the experimental group demonstrated gradual and continuous improvement. In addition, students’ thinking skills and academic achievement in the experimental group are discussed in depth.